2021
DOI: 10.1136/ijgc-2020-001764
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy in pregnant patients with cervical cancer: a Latin-American multicenter study

Abstract: ObjectiveTo describe oncologic and obstetric outcomes in patients diagnosed with cervical cancer during pregnancy who had a successful delivery after neoadjuvant chemotherapy.MethodsA multicenter retrospective review was conducted in 12 institutions from six Latin American countries, between January 2007 and December 2018. Data collected included clinical characteristics, neoadjuvant chemotherapy agents, treatment, obstetric and oncologic outcomes.ResultsThirty-three patients were included. Median age was 34 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Interestingly, the only patient who died of disease was the only one who received monochemotherapy with cisplatin and radical surgery following the cesarean section. The available, retrospective cohort studies confirm the excellent oncological outcomes of patients treated in pregnancy with NACT and CRH [ 12 , 13 ]. The outcomes of patients who decided to continue the pregnancy seems to be comparable to that of patients who chose to terminate it, and the prognosis of pregnant and non-pregnant patients seems to be similar [ 8 ].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Interestingly, the only patient who died of disease was the only one who received monochemotherapy with cisplatin and radical surgery following the cesarean section. The available, retrospective cohort studies confirm the excellent oncological outcomes of patients treated in pregnancy with NACT and CRH [ 12 , 13 ]. The outcomes of patients who decided to continue the pregnancy seems to be comparable to that of patients who chose to terminate it, and the prognosis of pregnant and non-pregnant patients seems to be similar [ 8 ].…”
Section: Discussionmentioning
confidence: 86%
“…To date, little and discordant data still exist in the literature on the management of CC in pregnancy, with considerable heterogeneity in terms of treatment, CT schedules, timing, and surgical procedures [ 7 , 9 , 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that early pregnancy chemotherapy is not associated with increased congenital abnormalities, while chemotherapy in mid to late pregnancy is associated with fetal growth restriction, low birth weight, and preterm labor (Mandic, et al,2020). However, several studies have shown that neoadjuvant chemotherapy in mid to late pregnancy is safe (Sparano, et al,2008;Zagouri, et al,2019) and is an effective alternative for achieving fetal survival (Lopez, et al,2021). Neoadjuvant chemotherapy can control tumor progression, delay the pregnancy week, promote fetal lung maturation, ensure maternal and fetal survival, and prevent lesion transfer during pregnancy (Mandic, et al,2020;Bernardini, et al,2022).Therefore, neoadjuvant chemotherapy is safe and effective in pregnant women with cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…All chemotherapy agents are potentially teratogenic and there is a potential long-term effect on the offspring. [15] The key factor in this situation is the relationship between the doctor's conscience and the patient's trust. [16] Decisions concerning the choice of the best management of ovarian cancer are very complex and difficult because of the conflict between the mother's and the fetus's wellbeing [17] ; thus, a multidisciplinary team consisting of an obstetrician, oncologist, pathologist, anesthesiologist, neonatologist and psychologist is mandatory.…”
Section: Discussionmentioning
confidence: 99%